Efeitos de variáveis de procedimentos de treino para o estabelecimento do controle contextual de relações condicionais e de equivalência - Castro, Tatiane Carvalho (Universidade Federal de São Carlos, 2013)
Studies about the effects of contextual control over equivalence classes have been conducted since the 1980s and a relevant question in this area, both in terms of experimental and applied research, is whether changes in contextual variables could result in changes in classes originally formed under different contextual variables. This research investigated, in four studies, the effects of procedures for establishing the contextual control of conditional relations and equivalence classes. The participants were undergraduate students. The stimuli used as sample and comparison were abstract figures and the contextual stimuli were represented by the colors of the background on which the stimuli were presented. In Study 1, we conducted a procedure for the formation of equivalence classes on backgrounds of red and blue colors. Later we conducted a test that showed the equivalence relations in the presence of contextual stimuli blue, red and green. The results showed that participants had responses consistent with the last equivalence class trained, independent of contextual stimulus. Study 2 replicated the previous study, but tests also showed baseline relations. The results obtained were similar to Study 1. Study 3, initially, partially replicated the procedure of previous studies, only for conditional relations AB and then tested the effects of a conditional discrimination training procedure interspersing the colors of the background. The results revealed that this procedure was most effective in setting the control contextual than those conducted in Studies 1 and 2. Study 4 investigated the effects of a interpersed training procedure for the establishment of the contextual control of recombined conditional relations. The procedure consisted of six phases. Phase1 was conducted a conditional discrimination training interspersing the colors of the background. In Phase 2, we carried out the test of relations trained in Phase1. In Phase 3, tests were conducted in which trials were included with a green background. Phase 4 included the symetry relations. Phase 5 presented the same relations were tested in Step 4, however the configuration of stimulus presentation on the computer screen was different. Finally, in Step 6, a test aimed to verify the abstraction of responding under contextual control, with new stimulus and background colors. The results suggest that the contextual control was established for some of the participants. Investigations about the baseline relations training, specifically the interspersed training , for establishing the contextual control is required to produce more robust results.
Keywords: Psicologia experimenta; Equivalência de estímulos; Reorganização de classes; Controle contextual; Treino intercalado; Relação condicional; Classe de equivalência; Equivalence class; Reorganizing classes; Contextual control; Conditional relations; Interspersed training; CIENCIAS HUMANAS::PSICOLOGIA